New Find of a Roman Boundary Wall in Golubić near Obrovac (Archaeologia Adriatica, 2014)
This work presents a rare find of a Roman boundary wall found recently in the village of Golubić near Obrovac. Remains of a wide drystone wall were preserved about 900 m in length spreading in a straight line from the canyon of the Krnjeza river in the east to the southern slope of the hill Gradina in the west. The wall was built by the Roman authorities during the 1st century AD in order to make a territorial boundary between the two Liburnian peregrine communities. Most likely it was Hadra (Smokovac in Krupa) and one of the communities with the center on the left bank of Zrmanja. Roman administration built boundary walls to solve territorial disputes and possible conflicts between the members of neighbouring communities usually caused by rights of pasture and cattle movements in the boundary areas.
Keywords: boundary walls; Liburnian peregrine communities; Hadra; Krupa; Zrmanja